Clinical utility of the Sport Concussion Office Assessment Tool 6 (SCOAT6) and other select multidomain assessments for subacute sport-related concussion - Kontos, A. P.; Zynda, A. J.; Trbovich, A. M.; French, J.; Kegel, N.; Burley, C.; Patel, S.; Mucha, A.; Womble, M. N.; Jennings, S.; Dollar, C. M.; Elbin, R. J.; et al. (Sports Medicine, 2025)
Background: There is a need for an empirically supported, clinically pragmatic set of multidomain tools for the subacute assessment of sport-related concussion in clinical settings. The Concussion in Sport Group recommended a new tool called the Sport Concussion Office Assessment Tool 6 (SCOAT6) for a subacute (3-30 days) sport-related concussion assessment; however, it has yet to be empirically validated. Objective: We aimed to evaluate the clinical utility of the SCOAT6 compared to select multidomain assessments comprising the Concussion Clinical Profile Screening (CP Screen), Immediate Post-concussion Assessment and Cognitive Testing (ImPACT), and Vestibular/Ocular Motor Screen (VOMS) in identifying athletes with sport-related concussion from healthy controls. Methods: There were 134 participants (aged 13-29 years) within 3-30 days of sport-related concussion and 67 healthy controls who completed the SCOAT6 recommended components (e.g., Post-Concussion Symptom Inventory [PCSI], verbal cognitive tests, orthostatic vital signs, modified Balance Error Scoring System [mBESS], timed tandem gait, and modified VOMS [mVOMS]), optional screeners (e.g., Generalized Anxiety Disorder-7 [GAD-7], Patient Health Questionnaire-2 [PHQ-2], Athlete Sleep Screening Questionnaire [ASSQ]), and other select multidomain assessments (e.g., CP Screen, ImPACT, VOMS) at their initial visit. Results: PCSI, mVOMS, and timed tandem gait demonstrated acceptable to outstanding utility (area under the curve [AUC] = 0.73-0.91) to identify sport-related concussion from controls, while the remaining SCOAT6 components demonstrated unacceptable utility (AUC < 0.70). Nearly all CP Screen, ImPACT, and VOMS components demonstrated acceptable to outstanding utility (AUC = 0.72-0.97), except for CP Screen anxiety/mood, ImPACT reaction time, and VOMS near point of convergence distance (AUC < 0.70). Conclusions: The PCSI, timed tandem gait, and mVOMS components of the SCOAT6 were useful in identifying sport-related concussion. However, verbal cognitive tests, orthostatic vital signs, and clinical balance components were not useful for this purpose. The CP Screen, additional items from the full version of the VOMS, and ImPACT memory and processing speed were also useful in identifying sport-related concussion and should be included in a multidomain approach for the subacute assessment of sport-related concussion.